Analysis of Extractives in Liquid and Headspace Samples of Silver Fir Using Gas Chromatography Coupled with a Mass Selective Detector - Viljem Vek; Ida Poljanšek; Urša Osolnik; Primož Oven (Drvna Industrija)
The main objective of the study is to present a chromatographic method that allows rapid and accurate quality control of extractives in liquid and headspace samples of wood and bark of European silver fir (Abies alba Mill.). The chemical identity of silver fir extractives in liquid and headspace samples was investigated. Mature silver firs were harvested and samples of sapwood, heartwood, knotwood and bark were prepared. Liquid samples were obtained by solvent extraction at higher temperature and pressure, while the volatile extractives of silver fir tissues were collected by headspace sampling. The extractives in the liquid silver fir samples were silylated prior to chromatographic analysis. The samples were then measured using gas chromatography (GC) coupled with a mass selective detector (MSD). The samples were introduced into the GC-MSD system using the Automatic Liquid Sampler (ALS) and the Headspace Sampler (HS). A total of 55 compounds were detected in the silver fir wood and bark samples. The liquid samples consisted of a variety of carboxylic/dicarboxylic acids, sugars with sugar alcohols (inositols) and sugar acids, with citric acid, quininic acid and sucrose being the most frequently represented. The liquid bark samples contained mainly sugar-like compounds, while the knotwood extracts contained large amounts of phenolic compounds and lignans. D-pitinol was confirmed as the most characteristic GC-MSD peak of the silver fir extracts. Analysis of the headspace of silver fir revealed α-pinene, camphene, Dlimonene, β-myrcene, ocimene, 2-bornanone or D-camphor and α-terpineol as the characteristic monoterpenes. It was shown that the presented GC-MSD method is a suitable analytical tool for the chemical screening of lowmolecular weight compounds in both liquid and headspace samples of wood and bark. However, the analysis of higher molecular weight extractives requires a different analytical approach supported by other analytical methods such as LC/MS.